Every little helps: exploring meat and animal product consumption in the Tesco 1.0 dataset - Rakefet Cohen Ben-Arye; Christopher Bryant; Katharina Hofmann (CABI Agriculture and Bioscience)
Abstract The production and consumption of meat and animal products have been associated with an array of ethical, health, and environmental issues. While social scientists have increasingly focused on meat reduction and the promotion of meat alternatives in recent years, and have identified a number of regional, seasonal, and sociodemographic variations in consumption, empirical work is often based on self-reported data. To build a greater understanding of actual dietary habits, we seek to provide analysis based on real food purchase data by aggregating data from different sources. To this end, we explore the consumption of meat and animal products in the Tesco 1.0 dataset, an Open Access dataset representing 420 million food item purchases made by 1.6 million loyalty card users at 411 Tesco stores across Greater London in 2015. The data is aggregated most granularly at the level of monthly purchase of 11 broad food categories in 4833 lower super output areas (LSOA—the smallest geographic area). We represented the consumption of meat and animal products graphically for each month of the year and for each of 33 London boroughs. In general, we found that the spring and summer months had the highest consumption of meat and animal products, including poultry, and this decreased in autumn. We also combined the Tesco 1.0 dataset with datasets from the London Datastore (a free and open data-sharing portal that provides over a thousand datasets to understand the city and develop solutions to its problems), and identified several demographic factors as predictors for the meat consumption. Contrary to our hypothesis, areas with older, lower education, and more conservative populations had a lower proportion of meat consumed. In line with our hypotheses, a lower proportion of meat consumed could be observed in areas with higher population density, better health, and more Hindus. The purpose of this paper is to add to knowledge on regional, seasonal, and sociodemographic variations in animal product consumption, as well as provide a valuable overview of animal product consumption using a novel data source that comprises actual purchase data rather than self-reported consumption.